(untitled) (CIPEEX, 2026)
Summary INTRODUCTION: Child-adolescent mental disorders have become increasingly prevalent, demanding effective therapeutic interventions. Among these, psychopharmacology has stood out in the management of conditions such as Attention Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorder (ASD) and Major Depressive Disorder (MDD). OBJECTIVE: To identify the most frequent mental disorders in children and adolescents treated at the Child and Adolescent Outpatient Clinic (ACA), in Anápolis-GO, between 2021 and 2024, and analyze the psychopharmacological therapies used. METHOD: Descriptive, analytical and retrospective study, based on the documentary analysis of 100 medical records of patients treated between March 2021 and April 2024. Sociodemographic data, diagnoses and prescribed psychotropic drugs were collected. RESULTS: Of the 100 medical records analyzed, 21 presented more than one psychiatric diagnosis. Thus, based on a total of 121 recorded diagnoses, we concluded that the most prevalent disorders were ADHD 30.57% (37/121), TDM 13.22% (16/121 cases) and ASD 12.40% (15/121), the other less prevalent disorders, detailed throughout the work, totaled 51.81% (62/121). Methylphenidate was the most prescribed drug for ADHD, Risperidone for ASD, and Fluoxetine for TDM. Children under 10 years old were mainly treated with Risperidone and Aripiprazole; between 10 and 15 years old, Methylphenidate predominated; in adolescents aged 16 to 18 years, Fluoxetine was more frequent. There was a greater use of monotherapy for ADHD and polypharmacy for ASD. CONCLUSIONS: The analysis reveals a consistent pattern of psychopharmacological prescription according to the disorder and age group. The data can assist in the standardization of clinical conduct and promote the rational use of drugs in child and youth mental health care. Keywords: Mental disorders; Psychotropic drugs; Child and adolescent mental health.